2018
DOI: 10.1111/ejn.14074
|View full text |Cite
|
Sign up to set email alerts
|

Changes of motor corticobulbar projections following different lesion types affecting the central nervous system in adult macaque monkeys

Abstract: Functional recovery from central nervous system injury is likely to be partly due to a rearrangement of neural circuits. In this context, the corticobulbar (corticoreticular) motor projections onto different nuclei of the ponto‐medullary reticular formation (PMRF) were investigated in 13 adult macaque monkeys after either, primary motor cortex injury (MCI) in the hand area, or spinal cord injury (SCI) or Parkinson's disease‐like lesions of the nigro‐striatal dopaminergic system (PD). A subgroup of animals in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 87 publications
(247 reference statements)
8
46
0
Order By: Relevance
“…Further analyses using such techniques may reveal the roles of both the SMA and the PMv in motor functional recovery. It is also important to identify the subcortical structures that, after infarction of the posterior internal capsule, are involved in motor recovery in concert with the intact motor cortical areas, as suggested by previous studies of motor recovery after unilateral M1 lesioning [38][39][40] .…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses using such techniques may reveal the roles of both the SMA and the PMv in motor functional recovery. It is also important to identify the subcortical structures that, after infarction of the posterior internal capsule, are involved in motor recovery in concert with the intact motor cortical areas, as suggested by previous studies of motor recovery after unilateral M1 lesioning [38][39][40] .…”
Section: Discussionmentioning
confidence: 99%
“…The materials and methods are similar to those reported in recent publications related to the corticobulbar (corticoreticular) and corticotectal projections Fregosi et al, , 2018Fregosi et al, , 2019. Briefly, surgeries were performed under sterile conditions in anesthetized animals.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) intoxication model, producing Parkinson's disease (PD)-like symptomatic macaque monkeys, it was shown that a cellular therapy referred to as autologous neural cell ecosystem (ANCE) improves recovery of motor control (Bloch et al, 2014;Borgognon et al, 2017Borgognon et al, , 2019. Subsequently, in four of such MPTP intoxicated monkeys subjected to ANCE therapy, tracing studies showed that the corticobulbar (corticoreticular) projections were significantly reduced as compared to intact monkeys (Fregosi et al, 2018), whereas the corticotectal projection was much less affected (Fregosi et al, 2019). As far as the corticosubthalamic projection (CSTP) is concerned, a loss of the hyper direct pathway was reported in PD mice (Chu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, work with cortical-or spinal cord-injury models suggests that brainstem circuits in the reticular formation and red nucleus gain functional importance under these compromised experimental conditions. Proposed mechanisms contributing to hand function recovery after injury include axonal sprouting by cortical axons at the brainstem level and/or by reticulospinal axons in the spinal cord, thus compensating for the reduction or lack of cortical access to the spinal cord (Baker 2011, Baker et al 2015, Fregosi et al 2018. Here, we review progress on the identification, anatomical organization, and function of neuronal circuits connecting the brainstem and spinal cord bidirectionally, with a role in shaping skilled forelimb behaviors in the uninjured nervous system.…”
Section: Brainstem and Spinal Circuits For The Control Of Skilled Formentioning
confidence: 99%